Design/type : a seductive collection of alluring type designs - Burgess, Paul , 1969-; Seddon, Tony , 1965- (Page One, 2012)
"Featuring a curated collection of about 500 exquisite designs, along with essays from top designers about the essence and importance of good typography in design, Design/Type is an insightful resource filled with mini-workshops that dissect several featured projects and highlight the effectiveness of the type treatments. The first in a new series, this informative sourcebook offers the best of typography in practice and is an essential resource for students and professionals alike"-- Provided by publisher